2012
DOI: 10.1016/j.thromres.2012.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide (CO)-releasing molecule-derived CO regulates tissue factor and plasminogen activator inhibitor type 1 in human endothelial cells

Abstract: Introduction: Heme oxygenase-1 (HO-1) is the rate limiting enzyme that catalyzes the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…Furthermore, it was shown that CORM-2 suppressed pro-thrombotic (tissue factor, TF) and anti-fibrynolytic (PAI-1) activities of the endothelium stimulated by inflammatory cytokines (TNF-α) and regulated activation of MAPKs and NF-kB signaling pathways [15]. However, the target responsible for the beneficial action of CO in the endothelium remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was shown that CORM-2 suppressed pro-thrombotic (tissue factor, TF) and anti-fibrynolytic (PAI-1) activities of the endothelium stimulated by inflammatory cytokines (TNF-α) and regulated activation of MAPKs and NF-kB signaling pathways [15]. However, the target responsible for the beneficial action of CO in the endothelium remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms through which the donor HO-1 A/A or A/T genotype (plausibly associated with the higher inducibility of HO-1) exerts its beneficial effects remains to be determined. HO-1 is only marginally produced in the resting state, but is rapidly and highly induced in response to various oxidative stresses (e.g., organ and tissue damage and infection), and acts as an anti-inflammatory and cytoprotective protein [7,[9][10][11]15,31,32]. Evidence of HO-1 induction improving the survival outcomes after allo-HSCT has been demonstrated in previous studies using mouse models [31,33].…”
Section: Discussionmentioning
confidence: 90%
“…Heme oxygenase-1 (HO-1), also known as a 32 kDa heat-shock protein, is an intracellular enzyme that catalyzes the degradation of heme into biliverdin, ferrous iron, and carbon monoxide (CO), with biliverdin being subsequently catabolized into bilirubin [7][8][9][10][11]. HO-1 is highly induced in response to various stress signals, such as free heme and hemoglobin, inflammatory cytokines, ischemia, endotoxins, irradiation, and mucosal damage [9][10][11][12][13][14][15][16]. HO-1 thus exerts cytoprotective effects on endothelial cells through ant-oxidative, anti-inflammatory, anti-apoptotic, and anti-thrombotic effects, which are coordinated with heme metabolites of CO and bilirubin.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, transition metal carbonyls have been identified as the potential to facilitate the pharmaceutical use of CO by delivering it to the tissues and organs of interest 13, 26. Studies elucidated that CORM-2 suppressed LPS-induced inflammatory responses in human umbilical vein endothelial cells (HUVECs), peripheral blood mononuclear cells (PBMCs) and macrophages 27, 28. Similarly, the results reported in our laboratory and others confirmed that CO derived from CORMs rescued mice from lethal sepsis induced by LPS or CLP 16-18.…”
Section: Discussionmentioning
confidence: 99%